2018
DOI: 10.1002/ase.1827
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Frontline Near‐Peer Teaching in a Modern Medical Curriculum

Abstract: Within medical education a reduction in curriculum time for subjects, such as anatomy puts pressure on educators to ensure the same learning outcomes are conveyed in less time. This has the potential to impact negatively on student experience. Near‐peer teaching (NPT) is often praised as an effective revision tool, but its use as a frontline teaching resource remains unreported. The study explores the potential for NPT to promote delivery of learning outcomes and maximize student experience within a neuroanato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 50 publications
2
21
0
5
Order By: Relevance
“…Our findings indicate that not only did the student learners experience knowledge gain, evidenced through studies using pre- and post-testing methods (Parton 2017), but students also trusted the knowledge of the near-peer teachers as much as the knowledge of faculty staff (Harrison and others 2017; Parton 2017). Furthermore, student learners felt strongly that the near-peer teachers would improve their performance in end of module assessments (Harrison and others 2017), and it has been shown that near-peer teachers improve student perceptions of their own knowledge (Hall and others 2014). These data suggest that student teachers are highly valued by student learners and may be seen as role models.…”
Section: Near-peer Teachingmentioning
confidence: 72%
“…Our findings indicate that not only did the student learners experience knowledge gain, evidenced through studies using pre- and post-testing methods (Parton 2017), but students also trusted the knowledge of the near-peer teachers as much as the knowledge of faculty staff (Harrison and others 2017; Parton 2017). Furthermore, student learners felt strongly that the near-peer teachers would improve their performance in end of module assessments (Harrison and others 2017), and it has been shown that near-peer teachers improve student perceptions of their own knowledge (Hall and others 2014). These data suggest that student teachers are highly valued by student learners and may be seen as role models.…”
Section: Near-peer Teachingmentioning
confidence: 72%
“…As a result of the exponential growth in medical knowledge, and the resultant constraints on medical curricula (Johnson et al, 2012), the amount of time devoted to teaching anatomy has declined significantly (Drake et al, 2009). Considering the difficulty in understanding the structural orientation and function of the brain (Javaid et al, 2018; Tarolli and Jozefowicz, 2018), along with the decreased time offered to core subjects, such as neuroanatomy, peer teaching can provide a means of effectively improving the instructor‐student ratios, and providing quality small team‐based learning experiences that can accommodate large number of students within the new time constraints (Johnson et al, 2012; Freret et al, 2017; Harrison et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Peer teachers (PTs) who are only slightly more advanced in their educational stage than the learners are referred to as near‐PTs (Whitman and Fife, 1988; Bulte et al, 2007; Harrison et al, 2019). In gross anatomy, near‐peer teaching is used predominantly for laboratory sessions, where students who have recently passed the course (near peers) facilitate laboratory sessions by working with junior students in small team groups on the available material (Johnson et al, 2012; Hall et al, 2013; Dickman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overwhelmingly, the evidence illustrates that medical students who are taught clinical skills through peer teaching perform just as well, if not better, in comparison to those taught without peer teachers (Yu et al 2011;Harrison et al 2019). Key advantages for peer learners include an improved learning atmosphere (Harrison et al 2019), reporting their peer tutors to be an accommodating addition to the existing teaching (Naeger et al 2013) and disclosing reprieve from exam-related concerns (Lydon et al 2017). Those senior students who teach also advance both academically and professionally (Burgess et al 2016;Khaw and Raw 2016;Wankiiri-Hale et al 2020).…”
Section: Introductionmentioning
confidence: 99%